Satisfaction with Life of Schizophrenia Outpatients and Their Caregivers: Differences between Patients with and without Self-Reported Sleep Complaints. (27th October 2013) - Brissos, Sofia; Afonso, Pedro; Cañas, Fernando; Bobes, Julio; Bernardo Fernandez, Ivan; Guzman, Carlos
Abstract : Patients with schizophrenia often present sleep complaints, but its relationship with general satisfaction with life (SWL) and burden for caregivers has been understudied. We aimed to assess the differences in SWL between patients with and without self-reported sleep disturbances and that of their caregivers. In a noninterventional study, 811 schizophrenia adult outpatients were screened for their subjective perception of having (or not) sleep disturbances and evaluated with the Brief Psychiatric Rating Scale (BPRS) and the Pittsburgh Sleep Quality Index (PSQI). Patients self-reporting sleep disturbances were significantly more symptomatic (P < 0.001 ), presented significantly worse family support (P = 0.0236 ), and self-reported worse SWL in all domains. Caregivers of patients with schizophrenia self-reporting sleep disturbances also reported worse SWL in all domains, as compared to caregivers of patients without subjective sleep disturbances. Patient and caregivers' SWL was significantly correlated to patients' quality of sleep (P < 0.0001 for all domains). Patient' and caregivers' SWL was negatively affected by patients' poor quality of sleep. We found that patients self-reporting sleep disturbances showed greater symptom severity, worse quality of sleep, worse SWL, and less caregiver support. SWL was also worse for caregivers of patients with schizophrenia reporting sleep disturbances.